A Robust Driver for RGB LEDs - Shaheer Shaida, Durrani; Abu Zaharin, Ahmad; Bakri, Hasan; Mohd Shafie, Bakar (IEEE, 2018)
For running applications based on RGB LEDs, a dc-dc buck converter associated with linear control is mostly used to manage the constant current of LED. In this paper, the driver to run RGB LEDs gives 180 mA constant outputs current and a PWM control scheme has been utilized, which determines the desired brightness levels with a dimming frequency of 10000 Hz. Previously there used to be a dimming option for dimming each array of LED color, through the dimming controller circuit; approximately 93%, 90% 93% efficiencies, were found for the green, red and blue color LEDs' arrays respectively. A digital controller based on PID controller has been created, with the option of using digital dimming by using current mirroring with a transistor (for the intent of switching system). The proposed LED driver system contains the constant source of current to maintain the small drive voltage across the LEDs which lead in the reduction of power dissipation in the transistor, i.e., NPN, which eventually increases the efficiency of the whole system in return. With the application of the 12V supply voltage, the efficiencies of RGB LEDs are found up to 98.94%, 99.37%, and 99.37% correspondingly.